A Broken Conception of History from Nietzsche and Deleuze: Nihilism as A priori of Universal History - Martínez Reinoso, Rodrigo (Revista de Humanidades de Valparaíso, 2014)
In the present text there are exposed some central aspects of the critique realized by the French philosopher Gilles Deleuze to the historicism. From Friedrich Nietzsche’s work, specially of his Theory of the last man exposed in Thus Spoke Zarathustra and of his text “On the Use and Abuse of History for Life”, it is possible to accuse the character mystified of the ideas of progress, evolutionism and of the thought of the Illustration in which Hegel’s philosophy is inserted. Also some relations are established between the circular and linear conception of the history and his political and ethical connotations. And simultaneously the relation is underlined between history and myth from allusions to Plato, Kant and the Great Statement of the Modernity.